Pengaruh Mekanisme Good Corporate Governance Dan Pengungkapan Akuntansi Lingkungan Terhadap Kinerja Keuangan Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021 - Ema Yanti; Effendy, Lukman; Isnaini, Zuhrotul (Jurnal Riset Mahasiswa Akuntansi, 2024)
This research aims to determine the mechanism of Good Corporate Governance and Environmental Accounting disclosure on Company Financial Performance. Good Corporate Governance in the proxy mechanisms consists of board of commissioners, board of directors, audit committee and institutional ownership. Data was obtained from annual reports of manufacturing companies in the basic industrial and chemical sectors for 2019 - 2021. The total population was 79 companies, using purposive sampling techniques obtained as many 159 samples. Data were analyzed using panel data regression. The research results show that the board of commissioners, board of directors, audit committee and institutional ownership have no effect on the company's financial performance. And also environmental accounting disclosures have no effect on the company's financial performance.